Application of the Problem Based Learning Model in Indonesian Language Learning in Elementary Schools - Mardiyanto, Dwi; Wulandari, Retno Bety; Pratiwi, Veronica Unun; Nugrahaini, Farida (J-LELC: Journal of Language Education, Linguistics, and Culture, 2024)
The implementation of PBL in Indonesian language learning is explained in the form of steps taken by teachers during learning as well as the problems experienced by teachers in connection with the implementation of the problem-based learning model. Problem-based learning provides opportunities for students to participate in improving communication skills, exploring information and data, collaborating in groups, and thinking critically about problems. This is because PBL often takes problems related to students' real lives. The method used in this research is descriptive qualitative type. Research data includes observations and interviews with teachers at schools. Data collection methods involve observation, interviews, and documentation. Analysis of research data was carried out using a qualitative descriptive approach through three simultaneous steps, namely data reduction, data presentation and drawing conclusions. The findings from this research indicate that the use of the PBL model in Indonesian language learning is able to provide a level of interactivity, creating simulations where students can work together and collaborate in dealing with problems that are similar or similar to real life situations.